2015
DOI: 10.1007/s00431-015-2546-0
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal and cardiac muscle involvement in children with glycogen storage disease type III

Abstract: Myopathic changes are not uncommon in children with GSD III. Myopathic changes tend to occur in older age and are associated with higher CPK level. Cardiac muscle involvement is less common in this age group and may, on occasion, occur alone without skeletal muscle involvement. Despite mild degrees of affection in this age group, it is recommended to perform prospective annual screening using EMG and echocardiography in order to augment dietary therapy regimen to prevent progression to life threatening complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 11 publications
8
39
0
Order By: Relevance
“…The prevalence of cardiac involvement in GSD IIIa varies in the literature from 31 to 95% [3,16]. Mogahed et al [21] have found cardiac incidence in GSD IIIa patients to be low and independent from neuromuscular involvement, similar to our patient group, where 2 out of 6 had cardiomyopathy with variable CK levels. Rossi et al [5] and many other authors have shown the cardiac pathology of GSD IIIa to benefit from high-fat diet [5,18,19].…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence of cardiac involvement in GSD IIIa varies in the literature from 31 to 95% [3,16]. Mogahed et al [21] have found cardiac incidence in GSD IIIa patients to be low and independent from neuromuscular involvement, similar to our patient group, where 2 out of 6 had cardiomyopathy with variable CK levels. Rossi et al [5] and many other authors have shown the cardiac pathology of GSD IIIa to benefit from high-fat diet [5,18,19].…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, it has the potential to complement a gene therapy approach by ameliorating the cellular abnormalities associated with specific GSDs. In addition to liver complications, a high percentage of GSD III patients also eventually develop muscle weakness or heart complications 37, 38, 39. As expected, GYS2-1 treatment does not reduce glycogen accumulation in skeletal muscle due to the liver specificity of the GalNAc conjugation delivery approach (Figure S14).…”
Section: Discussionsupporting
confidence: 55%
“…CI in glycogen storage disease type-III may manifest as myocardial thickening or hCMP in most patients. 155) 156) Other cardiac manifestations include myocardial fibrosis, dCMP, or heart failure. 157) A single patient with premature coronary artery disease has been described in the literature.…”
Section: Resultsmentioning
confidence: 99%